If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4y + 360 = 0 Reorder the terms: 360 + 3x + 4y = 0 Solving 360 + 3x + 4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-360' to each side of the equation. 360 + 3x + -360 + 4y = 0 + -360 Reorder the terms: 360 + -360 + 3x + 4y = 0 + -360 Combine like terms: 360 + -360 = 0 0 + 3x + 4y = 0 + -360 3x + 4y = 0 + -360 Combine like terms: 0 + -360 = -360 3x + 4y = -360 Add '-4y' to each side of the equation. 3x + 4y + -4y = -360 + -4y Combine like terms: 4y + -4y = 0 3x + 0 = -360 + -4y 3x = -360 + -4y Divide each side by '3'. x = -120 + -1.333333333y Simplifying x = -120 + -1.333333333y
| a^2+3a+3=7 | | 2x-(3+x)= | | 4y^2+4y-28=0 | | 5z-4=8z-4z | | 9x+11-6x-2=2x+4+x+5 | | 2x^2-4x+22=0 | | 7c+18=-5c+78 | | 9p^2+2=11 | | 7(3s+4)=154 | | 5y-7=9+4(y-2) | | 27(x^4)+9+x=0 | | 7(3s+4)=158 | | 4(2l+2)=16 | | n*5= | | n*-5= | | 3(a-7)=15 | | x^2+7+12=(p+[1])(p+2) | | 54-n=25 | | 2n+9j=31 | | 6x+3(x+4)=8(x-3) | | U=3(8n+31)+7(n+1) | | 3(5m+2)-(4m+5)= | | B+45= | | 2x+3-7-x=2x-6-x+2 | | -4(x+3)-7=4x+13 | | n*5+8=7 | | (3z+1)=5+2 | | 2(r+h)-8=22 | | 2a+2=6-2a | | 0.03x+0.05(2500-x)=75 | | 5+22=n+16 | | 2(3x-1)=3-(-2-x) |